HUBUNGAN ANTARA QUICK OF BLOOD (QB) DENGAN PENURUNAN KADAR UREUM DAN KREATININ PLASMA PADA PASIEN CKD YANG MENJALANI HEMODIALISIS DI RSUD RADEN MATTAHER JAMBI - Erwinsyah Erwinsyah (Universitas Batanghari Jambi, 2014)
Effectiveness of hemodialysis can be seen from the decrease in urea and creatinine levels after hemodialysis. This effectiveness is achieved so that the necessary monitoring and regulation in the hemodialysis process, one of which is the setting and monitoring of blood flow velocity (quick of blood / qb) during hemodialysis. This study aims to determine the relationship between the quick and the impairment of blood urea creatinine post-hemodialysis CKD patients undergoing hemodialysis in the hemodialysis unit of a general hospital area raden Mattaher jambi.Object of this study is that CKD patients undergoing hemodialysis in the hemodialysis General Hospital Edinburgh Raden Mattaher total of 32 respondentsThe study design used was descriptive cross sectional Analytics. The samples in this research is by consecutive sampling,Results showed that more male patients than female by 66%, the average age was 51 years with the youngest age is 26 years old and the oldest 73 years of age. The study also showed an average qb is 190.586 ml / min. Value of the average predialysis urea was 132.8 mg / dl, after hemodialysis urea decreased by an average of 71.3 mg / dl (53.7%). Predialysis creatinine value is the average of 10.54 mg / dl, after hemodialysis creatinine decreased on average by 5.65 mg / dl. The results showed that there was no relationship between the value of qb with a decrease in post-hemodialysis urea in CKD patients undergoing hemodialysis (p = 0.799), there was no relationship between the value of qb with decreased creatinine ckd post hemodialysis in patients undergoing hemodialysis (p = 0.100).Hospitals need to make a permanent procedure on setting QB patients with standard rules refers to the patient's weight or dialser used, setting the right QB in order to increase the effect of adequacy of hemodialysis and hemodialysis adequacy regulation on the QB.Keyword: CKD; Kreatinin; Hemodialisis; Ureum; Quick Of Blood (Qb).